Effect of Garlic Fortified Drinking Water on Intestinal Parasites and Egg Laying Performance of Japanese Quail (Cortunix cortunix japonica) (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study investigated the effect of garlic fortified drinking water on intestinal parasites and egg laying performance of quails. Forty-five point-of- lay Japanese quails  (Cortunix cortunix japonica) were randomly allocated to three  treatments; T1 which served as the control had no test ingredients while T2 and T3 had 2g of  aqueous  garlic filtrate added to 1 litre of drinking water daily and 5g of the dewormer ((Bactro-expeller) added to  1 litre of their water at the 3rd and 5th week of the experiment  respectively.  . Each treatment had fifteen quails, with  three replications of five quails per replicate in a completely randomized design experiment. Intestinal mucosae of the quails were determined before and after the administration of the of the test materials. The trial lasted for eight weeks during which period the laying performance of the quails were monitored. Results showed presence of of intestinal parasites (93.75% Capillaria spp) for quails subjected to garlic treated water as well as 6.25% Ascaridia spp  for the control group while the dewormer (Bactro-expeller) treated group had no intestinal parasite record. There was no significant (P